A NOTE ON THE POLLEN OF WHITEODENDRON AND KJELL- BERGIODENDRON (MYRTACEAE) - KATHLEEN M. MCWHAE (REINWARDTIA, 1957)
A description has been given of the pollen grains of Whiteodendron moultonianum and Kjellbergiodendron celebicum. After this the relationships of both are discussed.